The formation of tubular seep carbonate deciphered from mineralogical and geochemical characteristics: an example from the South China Sea - Wei, Jiangong; Miao, Xiaoming; Gan, Kailong; Li, Jiangtao; Li, Jiwei; Liu, Xiting; Xu, Hengchao; Chen, Shun; Ta, Kaiwen; Wan, Zhifeng; Wu, Tingting (Frontiers in Marine Science, 2024)
As a special type of seep carbonate, the many details concerning formation mode and mechanism of tubular seep carbonates are rarely reported. Here, new geochemical and mineralogical data of tubular seep carbonate (SQW-65) are reported. Sample SQW-65 has anomalously negative δ 13 C values and positive δ 18 O values, which suggest dissociation of gas hydrate. Meanwhile, almost all the sub-samples show either no Ce anomaly (0.77